The sacraments of the law and the law of the sacraments - Hahn, Judith 1978- (Cambridge, United Kingdom New York, NY Cambridge University Press, 2023)
'Sacramentality' can serve as a category that helps to understand the performative power of religious and legal rituals. Through the analysis of 'sacraments', we can observe how law uses sacramentality to change reality through performative action, and how religion uses law to organise religious rituals, including sacraments. The study of sacramental action thus shows how law and religion intertwine to produce legal, spiritual, and other social effects. In this volume, Judith Hahn explores this interplay by interpreting the Catholic sacraments as examples of sacro-legal symbols that draw on the sacramental functioning of the law to provide both spiritual and legal goods to church members. By focusing on sacro-legal symbols from the perspective of sacramental theology, legal studies, ritual theory, symbol theory, and speech act theory, Hahn's study reveals how law and religion work hand in hand to shape our social reality
Introduction -- Sacraments in law and religion -- The ritual frame of sacraments -- Sacraments as speech acts -- Conclusion.
Title from publisher's bibliographic system (viewed on 13 Nov 2023)
Keywords: Sacraments (Canon law)